An experimental and kinetic modeling study of the autoignition delay times of triethyl phosphite - Bruce, Frederick Nii Ofei; Gao, Yuke; He, Ruining; Zhu, Zhihan; Wang, Xin; Zhao, Yilin; Jia, Mengmeng; Xie, Jiaxin; Bai, Xin; Taufiq-Yap, Yun Hin; Zhou, Chong wen; Curran, Henry; et al. (Elsevier, 2026)
Organophosphorus compounds (OPCs) are effective flame inhibitors due to their gas-phase radical-scavenging chemistry. However, the autoignition behavior of triethyl phosphite (TEPI, P(OC2H5)3), a trivalent organophosphorus compound, has not previously been characterized. This work presents the first experimental and kinetic modeling study of TEPI autoignition, addressing a key gap in the combustion chemistry of organophosphorus compounds. Ignition delay times (IDTs) of TEPI/air mixtures were measured behind reflected shock waves in a high-pressure shock tube at temperatures of 1000–1600 K, pressures of 5–10 bar, and equivalence ratios of φ = 0.1 and 0.5. A detailed TEPI oxidation mechanism was developed using high-level quantum chemistry, canonical transition-state theory with tunneling corrections, and RRKM/master-equation analysis, yielding over 40 TEPI-specific reactions that were integrated into a validated C0–C3 hydrocarbon/phosphorus base mechanism. The measured IDTs exhibit Arrhenius-type temperature dependence, strong pressure sensitivity, and longer ignition delays under leaner conditions. At 10 bar and φ = 0.5, TEPI ignites within 0.1 to 1 ms (1100–1500 K), approximately an order of magnitude faster than at 5 bar and φ = 0.1. The kinetic model reproduces the experimental IDTs within a factor of two across all conditions and identifies PO-containing intermediates (PO, HOPO, HOPO2) as key contributors to TEPI oxidation and inhibition of ignition. These results provide the first validated ignition dataset and chemical kinetic framework for TEPI, offering mechanistic insight into trialkyl phosphite combustion and establishing a foundation for extending trivalent phosphorus chemistry to future flame-inhibition and fire-suppression studies, where extinction and flame-speed measurements will be required.